(untitled) (Bangladesh Heart Journal, 2021)
Background: Intervention for bifurcation lesions is associated with increased risk of adverse events and includes acute side branch (SB) occlusion during main branch (MB) stenting. This acute occlusion of side branch can often be catastrophic for the patient. We here in describe our experience in National Institute of Cardiovascular Diseases and Hospital (NICVD), Dhaka, Bangladesh with a technique which can be incorporated into bifurcation stenting to reduce or almost eliminate the incidence of side branch occlusion or catastrophe. Methods: A prospective, observational, non-blinded study in patients from a single tertiary referral cardiac center National Institute of Cardiovascular Diseases & Hospital (NICVD), Dhaka, Bangladesh. Patients with an indication for percutaneous coronary intervention (PCI) of a denovo bifurcation lesion were screened. The study included 51 patients who underwent coronary angiogram in our institution and had bifurcation lesions suitable for single stent strategy between March 2017 to September 2018. Results: 51 patients with bifurcation lesion were included in the study and underwent a balloon embedded bifurcation stenting with a semi inflated balloon placed across the SB ostium. Angiographic success was achieved in all the patients but procedural success was achieved in 88.2% of the patients. TIMI 3 flow of main branch (MB) was achieved 96.08% and side branch (SB) was achieved 88.2%. Incidence of dissection was 5.9%, acute occlusion of SB was 2.0% and MACE was 3.9%. Mean fluoroscopy time and contrast volume was similar to that of conventional bifurcation stenting. The jailed SB balloon and wire could be successfully removed in all patients. Conclusion: The present study suggests that balloon embedded bifurcation stenting with a semi inflated balloon to protect the SB is feasible, with minimal procedural adverse events and successful in minimizing or almost eliminating the incidence of acute side branch occlusion or dissection as well as MACE. Bangladesh Heart Journal 2021; 36(1): 17-23